2019
DOI: 10.1007/s00213-019-5174-y
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic challenges for concurrent ethanol and nicotine consumption: naltrexone and varenicline fail to alter simultaneous ethanol and nicotine intake by female alcohol-preferring (P) rats

Abstract: Rationale and Objectives: Simultaneous alcohol and nicotine consumption occurs in the majority of individuals with alcohol use disorder (AUD) and nicotine dependence. Varenicline (Var) is used to assist in the cessation of nicotine use, while naltrexone (Nal) is the standard treatment for AUD. Despite evidence that ethanol (EtOH) and nicotine (NIC) co-use produces unique neuroadaptations, preclinical research has focused on the effects of pharmacotherapeutics on a single reinforcer. The current experiments exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…; Tizabi et al , ; Truitt et al ). Multiple reports have indicated that naltrexone and varenicline, the pharmacological ‘gold standards’ for treating AUD and nicotine dependence, both fail to alter the concurrent co‐administration of EtOH+NIC (Van Skike et al ; Waeiss, Knight, Hauser et al ; Maggio et al ). The current results provide clear preclinical data indicating that EtOH+NIC co‐administration results in a unique neurological cascade that is not observed following comparable exposure to EtOH or NIC alone.…”
Section: Discussionmentioning
confidence: 99%
“…; Tizabi et al , ; Truitt et al ). Multiple reports have indicated that naltrexone and varenicline, the pharmacological ‘gold standards’ for treating AUD and nicotine dependence, both fail to alter the concurrent co‐administration of EtOH+NIC (Van Skike et al ; Waeiss, Knight, Hauser et al ; Maggio et al ). The current results provide clear preclinical data indicating that EtOH+NIC co‐administration results in a unique neurological cascade that is not observed following comparable exposure to EtOH or NIC alone.…”
Section: Discussionmentioning
confidence: 99%
“…Varenicline (an α4β2 nicotinic acetylcholine receptor (nAChR) partial agonist) is approved for smoking cessation (Rollema et al, 2010), and naltrexone (an opioid receptor antagonist) and acamprosate (an NMDA receptor antagonist) are approved for alcohol use disorder (Franck and Jayaram-Lindström, 2013). Studies in alcohol-preferring female rats shows that varenicline reduces nicotine self-administration but has no effect on concurrent alcohol intake, and naltrexone reduces alcohol intake but has no effect on concurrent nicotine self-administration (Maggio et al, 2018;Waeiss et al, 2019), suggesting that monotherapy may be ineffective for combination alcohol and nicotine use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The microarray results were validated using RT-qPCR (Supplementary Fig. S9 ) as described elsewhere 6 , 7 . All reagents and kits used for quantitative reverse transcription polymerase chain reaction (RT-qPCR) were purchased from Applied Biosystems (Thermo Fisher Scientific, Carlsbad, CA, USA) unless stated otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…Their consumptions are highly linked to temporary behavioral changes, and when used together, they could result in synergistic adverse effects 4 , 5 . The rate of nicotine use has a positive correlation to the rate of alcohol use disorder (AUD) 6 – 8 . Substance use among pregnant women continues to be a major public health concern; 5% of pregnant women reported the use of one or more addictive substances during pregnancy and/or breastfeeding 9 .…”
Section: Introductionmentioning
confidence: 99%